The factors for residential properties overhang in Johor - Kasim, Rozilah; Tey, Chung Shien (Research in Management of Technology and Business, 2022)
In 2020, Johor recorded the highest number of residential overhangs at 7,030 units in Malaysia. However, the majority of the residential properties overhang in Johor were from the Johor Bahru district, accounting for 78.59% of the state’s overhang (5,525 units) in 2020. Despite there are many housing incentives announced by the government, the number of 2-3 storey semi-detached residential property overhang in Johor Bahru just decrease slightly from 378 units in 2019 to 313 units in 2020. Therefore, the objectives of this research are to investigate the factors that influence the 2-3 storey semi-detached residential property overhang in Johor Bahru, Johor. The data that related to research objectives were collected through a literature review of previous studies and distributing the online survey questionnaire form to the registered valuers, registered estate agents and housing developers in Johor Bahru in order to achieve the objectives of this research. The data analysis method of this study includes Multiple Regression analysis and Pearson Correlation analysis. The result shows that the price factor, location factor, housing loan factor, building factor and housing feasibility studies factor are the factors that influence 2-3 storey semi-detached residential properties overhang in Johor Bahru. Besides, the price factor is the most significant factor that influences the 2-3 storey semidetached residential properties overhang in Johor Bahru. In conclusion, this study can be used as a guideline to the housing developers and policymakers to plan suitable housing policies to improve the 2-3 storey semi-detached residential property overhang in Johor Bahru. In 2020, Johor recorded the highest number of residential overhangs at 7,030 units in Malaysia. However, the majority of the residential properties overhang in Johor were from the Johor Bahru district, accounting for 78.59% of the state’s overhang (5,525 units) in 2020. Despite there are many housing incentives announced by the government, the number of 2-3 storey semi-detached residential property overhang in Johor Bahru just decrease slightly from 378 units in 2019 to 313 units in 2020. Therefore, this research aims to investigate the factors that influence a 2-3 storey semi-detached residential property overhang in Johor Bahru, Johor. The data that related to research objectives were collected through a literature review of previous studies and distributing the online survey questionnaire form to the registered valuers, registered estate agents and housing developers in Johor Bahru in order to achieve the objectives of this research. The data analysis method of this study includes multiple Regression analyses and Pearson Correlation analyses. The results show that the price factor, location factor, housing loan factor, building factor and housing feasibility studies factor are the factors that influence 2-3 storey semi-detached residential properties overhang in Johor Bahru. Besides, the price factor is the most significant factor that influences the 2-3 storey semidetached residential properties overhang in Johor Bahru. In conclusion, this study can be used as a guideline to the housing developers and policymakers to plan housing policies to improve the 2-3 storey semi-detached residential property overhang in Johor Bahru.